Characterization of toughening mechanisms in UHPC through image correlation and inverse analysis of flexural results. (September 2021) - Mobasher, Barzin; Li, Anling; Yao, Yiming; Arora, Aashay; Neithalath, Narayanan
Abstract: The nature of cracking in flexural specimens made using ultra-high-performance concrete (UHPC) is studied in the context of mechanisms of enhanced strength and ductility. The effect of fibers on the suppression of cracking and the attendant toughening mechanisms are addressed at two different fiber contents to elucidate the strain-softening and strain-hardening responses. Results indicate that the first crack strength is directly related to the fiber content, with fibers extending the stable crack growth region at high fiber contents such that flexural strengths as high as 20 MPa are obtained. Fiber bridging results in resistance to crack growth, stabilization, as well as multiple crack formation, all of which contribute to toughening. Using a combination of experimental results, digital image correlation (DIC) measurements of crack extension, and an analytical model for the flexural response, the stress and strain distributions across the depth of the specimens are determined, leading to stress-crack width relationships, and consequently, the relationship between tensile and flexural stresses in fiber-reinforced UHPCs. The results are also used to determine the tensile and compressive strain and stress distributions. Using back-calculated tensile properties from the flexural response and the 3-D DIC results, crack width profile and the stress-crack width relationship in tension are obtained for UHPCs, leading to a comprehensive understanding required for the structural design using such high-ductility materials.